2007
DOI: 10.1001/archinte.167.7.649
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' Observations and Interpretations of the Influence of Religion and Spirituality on Health

Abstract: Background: In spite of a substantial body of empirical data, professional disagreement persists regarding whether and how religion and spirituality (hereinafter "R/S" and treated as a single concept) influences health. This study examines the association between physicians' religious characteristics and their observations and interpretations of the influence of R/S on health. Methods: A cross-sectional survey was mailed to a stratified, random sample of 2000 practicing US physicians from all specialties. Phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 22 publications
6
62
0
5
Order By: Relevance
“…The literature has clearly supported the benefits of religion on human wellbeing, while an extensive number of studies have revealed that religion has a valuable or protective effect on a variety of health outcomes (Chatters, 2000;Curlin et al, 2007;Ellison and Levin, 1998;Hall and Mdi, 2006;Jarvis and Northcott, 1987;Jones, 2004;Musick et al, 2000;Schnall et al, 2008). The predominant place of religion in health and illness was a constant theme in these studies and patients' views were strongly influenced by their religious convictions.…”
Section: Discussionmentioning
confidence: 93%
“…The literature has clearly supported the benefits of religion on human wellbeing, while an extensive number of studies have revealed that religion has a valuable or protective effect on a variety of health outcomes (Chatters, 2000;Curlin et al, 2007;Ellison and Levin, 1998;Hall and Mdi, 2006;Jarvis and Northcott, 1987;Jones, 2004;Musick et al, 2000;Schnall et al, 2008). The predominant place of religion in health and illness was a constant theme in these studies and patients' views were strongly influenced by their religious convictions.…”
Section: Discussionmentioning
confidence: 93%
“…The seventh article centered on "Physicians' observations and interpretations of the influence of religion and spirituality on health" and how such interpretations depend on physician's own R/S [7]. Sixty-three percent believed R/S influenced health of patients, 76% believed it could help patients cope with disease, give them a peaceful state of mind (75%) and provide emotional and practical help via the religious community (55%).…”
Section: Chronological Overview Of Existing Studies Using the Originamentioning
confidence: 99%
“…This article describes the development, contents, and first cross national comparisons based on an international research tool, first developed in 2002 and executed in 2003 with subsequent publications [1][2][3][4][5][6][7][8][9][10], translated into seven languages [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] and optimized in 2013. The data document the impact of Health Professionals' (HPs') religious and secular beliefs and values on the clinical encounter.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, physicians who consider religion most important were twice as likely to recommend full medical treatment and rated patient quality of life 30% higher; this was of similar magnitude to the effect of pain. This may be related to beliefs about the sanctity of life (36), the possibility of miracles (37), or deference to a higher power. We hypothesized that religious physicians would be less affected by cognitive deficits because of commitments regarding the sanctity of life, but the data indicate that religious and nonreligious physicians were similarly affected by the cognitive deficits variable.…”
Section: Discussionmentioning
confidence: 99%